The Analysis of Local Regression of Industrial Agglomeration on the Economic Growth in Indonesia - Santoso, Edy; Priyono, Teguh Hadi; Yunitasari, Duwi; Anggraini, Silvia (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
Economic growth is caused by various structural factors, including agglomeration industries and regional spending. This study aims to analyze the influence of industrial agglomeration on economic growth in Indonesia using the Geographically Weighted Panel Regression (GWPR) method. This method analyzes the spatially and temporally varied relationships between dependent and independent variables. This study considers spatial variation to investigate the variability of the economic growth model of each province in Indonesia. This study uses panel data with 34 provinces in Indonesia. Time range from 2017 to 2022. The results of the analysis show that the impact of industrial agglomeration on economic growth varies, with industrial agglomeration having a negative and significant effect on economic growth. Regional spending has a positive and significant influence on economic growth. These findings highlight the importance of policies adapted to regional conditions to maximize the benefits of industrial agglomeration and regional expenditure allocation in supporting sustainable economic growth in various provinces. This research provides important insights for policy makers and academics in designing more effective development strategies based on in-depth spatial analysis.